2011
DOI: 10.4161/viru.2.2.15015
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of managing fusariosis

Abstract: Fusarium is the second most frequent mold involved in fungal infections and is particularly important among immunocompromised patients. Culture methods and microscopy are still routinely used in clinical laboratories to identify Fusarium spp, and more sophisticated, timely, and effective methods for detecting Fusarium spp. in laboratory samples could improve the outcome of the patient. These investigational diagnostic approaches include serological assays and specific nested PCR assays that can yield positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 73 publications
5
62
0
1
Order By: Relevance
“…Species-specific differences in the susceptibility of Fusarium isolates was apparent in the MICs to amphotericin B, voriconazole, and posaconazole. In agreement with previous reports [16,37], amphotericin B was the most effective agent across all isolates. The European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and the European Confederation of Medical Mycology (ECMM) recommend amphotericin B and voriconazole as the first optional agents in the treatment of cases with fusariosis [18].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Species-specific differences in the susceptibility of Fusarium isolates was apparent in the MICs to amphotericin B, voriconazole, and posaconazole. In agreement with previous reports [16,37], amphotericin B was the most effective agent across all isolates. The European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and the European Confederation of Medical Mycology (ECMM) recommend amphotericin B and voriconazole as the first optional agents in the treatment of cases with fusariosis [18].…”
Section: Discussionsupporting
confidence: 81%
“…However, in the present study, these compounds were not effective against some of the species, sometimes indicating high degrees of intraspecific variability (Table 4). Some studies have reported that the MIC values in F. verticillioides were high for amphotericin B and low for posaconazole [16,37]. Similarly, we also observed activity of posaconazole against this species, but with a limited degree of confidence.…”
Section: Discussionsupporting
confidence: 45%
“…are important infectious filamentous fungi, it is particularly important among immunocompromised and neutropenic patients and is typically invasive and disseminated. Infection occurs mainly through inhalation of airborne conidia or via breaks in the skin due to trauma and/or burns (Muhammed et al, 2011). Twelve species were associated with infection; Fusarium solani was the most frequent (∼50% of cases), followed by Fusarium oxysporum (∼20%) and Fusarium verticillioidis and Fusarium moniliforme (∼10% each) (Nucci et al, 2013).…”
Section: Life-threatening Fungal Infectionsmentioning
confidence: 99%
“…Fusarium is an emerging opportunistic fungal pathogen, with a significant increase in cases among immunocompromised patients (Muhammed et al, 2011). Invasive fusariosis is the second most common form of mould mycosis after invasive aspergillosis and primarily affects patients with haematological malignancies, transplant recipients and those with prolonged neutropenia (Muhammed et al, 2011;Nucci & Anaissie, 2007).…”
Section: Introductionmentioning
confidence: 99%